EFEKTIVITAS LAYANAN KONSELING KELOMPOK DALAM MENINGKATKAN RESILIENSI SISWA SMP MUHAMMADIYAH 29 PADANGSIDIMPUAN - Nurhasanah Pardede; Siti Novrija Dalimunthe (Ristekdik : Jurnal Bimbingan dan Konseling, 2020)
The problem in this study is the low student resilience, due to the lack of the role of counseling guidance in schools. In this study to increase student resilience researchers used group counseling services. This study aims to obtain a picture of increasing student resilience in Padangsidimpuan 29 Muhammadiyah Middle School through group counseling services.The research method uses a quantitative approach, True Experimental Design in the form of Pretest-Posttest Control Grouf Design. The population in this study was 159 students, and 20 students as a sample, where 10 students from the experimental class group and 10 students from the control class group. The sample of the research used Simple Random Sampling technique, that is the research sample was obtained randomly. While the researchers' data analysis techniques used SPSS version 20.00 computer aids.The findings of this study indicate that the effectiveness of group counseling services in the experimental class before the treatment (pretest) was 1271 while after the treatment (posttest) increased to 1400. As for the results of research in the control class also showed that there was an increase in the first questionnaire (pretest) 1335 while the second questionnaire (posttest) increased to 1370.In the first hypothesis test results Z score of -2.805b with Asymp.sig (2-tailed) 0.005 ≤ 0.05. And on the results of the second hypothesis test Z score of -1.017b with Asymp.sig (2-tailed) 0.024 ≤ 0.05 so it can be concluded that the first and second hypotheses tested in this study can be accepted, because from the results of statistical analysis there are differences significant impact on student resilience before group counseling services are provided. So it can be concluded that the first and second hypotheses tested in this study were accepted "there is a significant difference in student resilience before and after group counseling services are provided".Based on the above findings, it can be concluded that the effectiveness of group counseling services can increase student resilience in SMP Muhammadiyah 29 Padangsidimpuan Academic Year 2015-2016.